2023
DOI: 10.1055/a-2039-5521
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Cyclization of Alkynyl Heteroarenes with a Norbornene Bridge

Abstract: In this study, Au(III)-catalyzed cyclization reactions of alkynyl norbornene derivatives were developed to provide benzofused (hetero)arenes with substitutions at the benzocyclic ring. The combination of Au(OAc)3 and AgNTf2 allowed for the annulation of (hetero)arenes by intramolecular hydro(hetero)arylation followed by retro-Diels–Alder reactions to afford fully conjugated benzofused (hetero)arenes in higher yields as compared to the yield obtained using our previously developed Pd(OAc)2-catalyzed protocol. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Earlier this year, Joo et al . uncovered the Au(III)‐catalyzed carbocyclization of thienyl‐alkynes bridged by norbornene ring 4.36 under high temperature (Scheme 31, eq 2) [170] . Under the reaction condition, the norbornene serves as a masked olefin by eliminating cyclopentadiene via retro‐Diels‐Alder reaction.…”
Section: Carbocyclization With Heteroaryl Nucleophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier this year, Joo et al . uncovered the Au(III)‐catalyzed carbocyclization of thienyl‐alkynes bridged by norbornene ring 4.36 under high temperature (Scheme 31, eq 2) [170] . Under the reaction condition, the norbornene serves as a masked olefin by eliminating cyclopentadiene via retro‐Diels‐Alder reaction.…”
Section: Carbocyclization With Heteroaryl Nucleophilesmentioning
confidence: 99%
“…Earlier this year, Joo et al uncovered the Au(III)catalyzed carbocyclization of thienyl-alkynes bridged by norbornene ring 4.36 under high temperature (Scheme 31, eq 2). [170] Under the reaction condition, the norbornene serves as a masked olefin by eliminating cyclopentadiene via retro-Diels-Alder reaction. Though the cyclization selectivity of this reaction follows 6-endo-dig regiochemistry, the positional selectivity varies with respect to the choice of anion in the gold catalyst.…”
Section: Carbocyclization With Heteroaryl Nucleophilesmentioning
confidence: 99%
“…Later, it was found that Au(III) catalysts also enabled cyclization of the same substrates with rearrangements depending on the positions of substituents, suggesting the different nature of the palladium catalytic system that does not generate the corresponding rearrangement products. 29 In addition to utilizing 1-PzPy in Pd-catalyzed reactions, the Joo group prepared a series of its -extended derivatives, known as PzNPy ligands, and applied them to Pdcatalyzed aerobic C-H alkenylation reactions of (hetero)arenes (Scheme 8). 15,30 Inspired by the Rh-catalyzed annulation of N-aryl pyrazoles developed by Miura and co-Scheme 6 Pd-catalyzed addition of arylboronic acids to cyanoacetate derivatives using the L4 ligand followed by hydrolysis and decarboxylation (Adhikari, 2015).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Later, it was found that Au(III) catalysts also enabled cyclization of the same substrates with rearrangements depending on the positions of substituents, suggesting the different nature of the palladium catalytic system that does not generate the corresponding rearrangement products. 29…”
Section: Applications Of 1-pzpy Ligandsmentioning
confidence: 99%